Fibre reinforced materials design & engineering applications : proceedings of the conference held in London, 23-24 March 1977. (Telford for the Institution of Civil Engineers, 1977)
Following on from the introduction, the chapters in this book focus on structure and material properties, highlight equilibrium conditions, and discuss hoop stresses in the plate and reinforcement.